The Influence of Using Mobile Learning "Wordwall" on the Critical Thinking Ability of Social Sciences Education Students at UIN Malang in the World History Course - Shobah, Wulan Nurus; Saputri, Afif Berlian; Fauziyah, Nailul (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Implementing an active and interactive learning model is crucial in the classroom to foster creativity and innovation, as seen in Mobile Learning Wordwall-based instruction. This study seeks to evaluate the effect of Mobile Learning Wordwall on students' critical thinking abilities. The method used was quasi-experimental, involving an experimental group and a control group, with a randomized pre-test post-test design. The study population comprised 5th-semester students from the Social Sciences Education program at UIN Malang. The sample included students from class B (control group) and class D (experimental group). The data analysis involved the Shapiro-Wilk normality test, the Levene homogeneity test, and hypothesis testing using a paired sample t-test. The results indicated a significant difference, with a p-value of 0.033 (<0.05), showing a meaningful difference between the pre-test and post-test results. This suggests that there was a notable influence on students' critical thinking abilities after implementing the Mobile Learning Wordwall method, compared to before the treatment.